2021
DOI: 10.1186/s12967-021-03020-z
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-based predictive biomarker of pathological complete response to neoadjuvant chemotherapy from histological images in breast cancer

Abstract: Background Pathological complete response (pCR) is considered a surrogate endpoint for favorable survival in breast cancer patients treated with neoadjuvant chemotherapy (NAC). Predictive biomarkers of treatment response are crucial for guiding treatment decisions. With the hypothesis that histological information on tumor biopsy images could predict NAC response in breast cancer, we proposed a novel deep learning (DL)-based biomarker that predicts pCR from images of hematoxylin and eosin (H&am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…By contrast, our proposed prediction system overcomes these limitations by a human prior knowledge guided deep learning attention framework with integrative use of serial pathology slides in multiple stains, achieving much better performance with an odds ratio higher than 50. Except for our previous study on this topic (34), only one study using deep learning for this prediction problem is found to our best knowledge (14). The Inception-V3 based CNN architecture is reported to predict pCR from NAC from pre-determined tumor epithelium regions in H&E pathology images, achieving 0.84 by AUC.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…By contrast, our proposed prediction system overcomes these limitations by a human prior knowledge guided deep learning attention framework with integrative use of serial pathology slides in multiple stains, achieving much better performance with an odds ratio higher than 50. Except for our previous study on this topic (34), only one study using deep learning for this prediction problem is found to our best knowledge (14). The Inception-V3 based CNN architecture is reported to predict pCR from NAC from pre-determined tumor epithelium regions in H&E pathology images, achieving 0.84 by AUC.…”
Section: Discussionmentioning
confidence: 97%
“…WSIs can serve as a decisive image modality that is already routinely used by pathologists for clinical diagnosis and prognosis in clinical settings. While there are few published studies on pCR prediction with pathology images (1214), the overall prediction performances are limited due to the use of a single information source, e.g., images from a single stain. With the rapid development of deep learning techniques, especially convolutional neural networks (CNNs), recent years have witnessed a significant advance not only in natural image processing research (15), but also in a wide range of biomedical image analysis tasks (16), such as abnormal region detection (17), cell segmentation (18), and survival prediction (19).…”
Section: Introductionmentioning
confidence: 99%
“…Recent fast ensemble deep learning techniques [60,61] can be applied in whole slide medical image analysis (f.e. predicting pCR from H&E stained whole slide images [62]) to reduce time and space overheads, at the expense of certain accuracy. However, we believe that the performance improvement is much more important in this task, so we choose some usual ensemble methods.…”
Section: Ensemble Learningmentioning
confidence: 99%
“…More recently, deep learning (DL) methods based on medical images were used to develop novel biomarkers that were found to be predictive of the prognosis and chemotherapy response [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we proposed an image-derived biomarker for predicting pCR in breast cancer, which revealed hidden predictive information from tumor epithelium [20]. Nevertheless, the tumor-associated stroma, .…”
Section: Introductionmentioning
confidence: 99%